A human resource management perspective of workplace bullying. Issue 2 (10th April 2017) - Rockett, Patrick; Fan, Susan K.; Dwyer, Rocky J.; Foy, Tommy
Abstract : Purpose: The purpose of this qualitative, multiple-case study paper is to determine whether Irish universities have policies and procedures to address workplace bullying; to determine the views of HR leaders regarding the efficacy of such policies; to explore the experience of HR leaders in the application of such policies; and, to explore which cost-reduction strategies Irish university HR leaders utilized to manage the consequences of workplace bullying. Design/methodology/approach: The participants for this multiple-case study consisted of senior manager grade staff with expertise in the area of study from all seven Irish universities. One on one interviews were conducted with participants to gain an understanding of their experience of dealing with workplace bullying. The analysis of their bullying policies and procedures provided insights about their experiences in the application of policy. Findings: The findings of this study may offer university leaders and a wider audience of managers an understanding of the effect that workplace bullying has on employees and on their organizations. Practical implications: This study may inform university and business leaders on how to address the problem of workplace bullying effectively. Originality/value: The findings from this study contribute to the discourse on workplace bullying and may help leaders to understand a phenomenon that costs their institutions a substantial amount in human capital leading to positive social change in their organizations.